2020
DOI: 10.1101/2020.07.20.211839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical measurement of physiological sodium currents in the axon initial segment

Abstract: In most neurons of the mammalian central nervous system, the action potential (AP) is triggered in the axon initial segment (AIS) by a fast Na+ current mediated by voltage-gated Na+ channels. The intracellular Na+ increase associated with the AP has been measured using fluorescent Na+ indicators, but with insufficient resolution to resolve the Na+ current in the AIS. In this article, we report the critical improvement in temporal resolution of the Na+ imaging technique allowing the direct experimental measurem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Furthermore, we found that the kinetics of sodium and calcium influx were indeed identical, but that calcium influx lagged sodium influx in ways that were consistent with sodium and calcium influx occurring on the rising and falling phases of the AP, respectively. These results are consistent with studies using high-speed optical imaging, where sodium influx occurs during the rising phase of the AP (Filipis and Canepari, 2020), whereas calcium influx occurs during the falling phase of the AP in the AIS or AIS-like regions of AP initiation (Hanemaaijer et al, 2020; Pressler and Strowbridge, 2019). Furthermore, we observed consistent results at both room temperature and physiological temperatures with two different sodium-sensitive indicators and two different calcium-sensitive indicators, suggesting that calcium influx occurs during Ca V -mediated tail currents on the falling phase of the AP in the axon, regardless of temperature (Kawaguchi and Sakaba, 2015; Pressler and Strowbridge, 2019; Rowan et al, 2014; Sabatini and Regehr, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we found that the kinetics of sodium and calcium influx were indeed identical, but that calcium influx lagged sodium influx in ways that were consistent with sodium and calcium influx occurring on the rising and falling phases of the AP, respectively. These results are consistent with studies using high-speed optical imaging, where sodium influx occurs during the rising phase of the AP (Filipis and Canepari, 2020), whereas calcium influx occurs during the falling phase of the AP in the AIS or AIS-like regions of AP initiation (Hanemaaijer et al, 2020; Pressler and Strowbridge, 2019). Furthermore, we observed consistent results at both room temperature and physiological temperatures with two different sodium-sensitive indicators and two different calcium-sensitive indicators, suggesting that calcium influx occurs during Ca V -mediated tail currents on the falling phase of the AP in the axon, regardless of temperature (Kawaguchi and Sakaba, 2015; Pressler and Strowbridge, 2019; Rowan et al, 2014; Sabatini and Regehr, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, we found the high basal fluorescence of SBFI resulted in significant photo-toxicity when the laser was parked at single sites. Therefore, we made use of a relatively new sodium-sensitive dye, ING-2, which reports increases in sodium concentration with an increase in fluorescence intensity without a change in emission spectra (Filipis and Canepari, 2020). Sodium influx was imaged in sets of 5 sites each 0.5 µm apart, as done for calcium pointscan imaging.…”
Section: Temporally Distinct Ap-evoked Sodium and Calcium Dynamics In The Aismentioning
confidence: 99%
“…Moreover, these events tended to precede AP onset as measured in the soma (median = -0.05 ms, IQR = -0.3625-0.1 ms). This may be due in part to the conduction delay between the AIS site of AP initiation and the soma (Kole et al, 2007;Rowan et al, 2014), and in part to subthreshold sodium influx before AP onset (Filipis and Canepari, 2020).…”
mentioning
confidence: 99%
“…In contrast, Na + remains mostly free in the cytosol, and it spatially equilibrates by diffusion before being extruded by the cell. In the case of the AIS of L5 pyramidal neurons, during a single AP, the contribution of longitudinal diffusion to the fast Na + kinetics is marginal (Filipis & Canepari 2020). However, in principle, diffusion cannot be ignored in other systems.…”
Section: Commentarymentioning
confidence: 99%
“…However, more recently, the Na + indicators Asante NaTRIUM Green‐2 (ANG‐2) (Miyazaki & Ross, 2015; Miyazaki, Lisman, & Ross, 2019) and ION NaTRIUM Green‐2 (ING‐2; commercially available from Ion Indicators) have been shown to provide a significant improvement in the signal‐to‐noise ratio (SNR) compared to SBFI. Combined with the latest technology in acquisition systems and lasers (Filipis et al., 2018), we recently measured Na + signals in the AIS at 10 kHz (Filipis & Canepari, 2020), i.e., at a temporal resolution comparable to that of optical AP recordings using voltage‐sensitive dyes (Popovic et al., 2015). Similar to the optical measurement of dendritic Ca 2+ currents (Jaafari & Canepari, 2016; Jaafari, De Waard, & Canepari, 2014; Jaafari, Marret, & Canepari, 2015), the Na + current was extracted by calculating the time derivative of the Na + transient.…”
Section: Introductionmentioning
confidence: 99%